Identifikasi Konsep Arsitektur Tradisional Aceh Pada Bangunan Pemerintahan di Banda Aceh (Studi Kasus: Kantor Gubernur Aceh) - Yuda Elfira; Zia Faizurrahmany El Faridy; Riza Aulia Putra (Prodi Arsitektur, Fakultas Sains dan Teknologi bekerja sama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Abstract. Nowadays, there are many new office buildings built in Aceh, thus are for supporting the public service functions carried out by the Government of Aceh. The design of a government office building is a representation of the Government or a region. According to Saiful Anwar (2016), the Aceh Governor's office is one of the buildings that applies local Acehnese wisdom, namely elements from traditional Aceh houses (Rumoh Aceh). The Aceh Governor's office was built in 1990 and initially consisted of six building blocks, two of the building of this office complex were damaged by the tsunami in 2004 and then renovated afterward. Since the beginning, the Governor's office has undergone several changes and renovations due to the disaster, and during the renovation process adjustments were also made to the needs and functions of the building. The researcher aims to examine how traditional architectural values are applied to the Aceh Governor's Office Building in the current situation. The research was conducted by using the observation and interview methodologies. The variables being studied from the design of the Aceh Governor's Office are the physical elements of the building such as plans, orientation, appearance, carvings, and other finishing elements. The results of the study provide an illustration that the Aceh Governor's Office Building is a reflection of the combination of the values of Traditional Acehnese Architecture and Modern Architecture that developed in Aceh in the early days of this building being built. However, this study also found that there were two masses of buildings that had undergone renovation after the Tsunami disaster in 2004 that did not apply Acehnese architecture at all in their designs.